Virtual neuromuscular ultrasound courses during COVID‐19 pandemic: Leveraging technology to enhance learning opportunities. Issue 1 (24th September 2021) - Tawfik, Eman A.; van Alfen, Nens; Cartwright, Michael S.; Inkpen, Peter; Kerasnoudis, Antonios; Lieba‐Samal, Doris; Winter, Natalie; Walker, Francis O.
Abstract: Introduction/Aims: Hands‐on supervised training is essential for learning diagnostic ultrasound. Unfortunately, the coronavirus disease 2019 (COVID‐19) pandemic led to suspension of in‐person training courses. As a result, many hands‐on training courses were converted into virtual courses during the pandemic. Several reports regarding virtual ultrasound courses exist, but none has addressed virtual neuromuscular ultrasound courses, their design, or participants' views of this form of training. Therefore, the aims of this study were: (1) to determine the feasibility of conducting virtual neuromuscular ultrasound courses during the COVID‐19 pandemic; and (2) to report the positive and negative aspects of the courses through the analyses of the responses of post‐course surveys. Methods: Two virtual neuromuscular ultrasound courses, basic and intermediate level, were conducted by the Egyptian Neuromuscular Ultrasound society during August 2020. Post‐course, the attendees were directed to an electronic survey that consisted of eight questions. Ninety‐three responses (23.8%) were obtained from the survey of the basic course and 156 responses (44.4%) were obtained from the survey of the intermediate course. Results: Ninety‐eight percent of the respondents to basic course surveys, and 100% of the respondents to the intermediate course survey found the courses useful or very useful. Discussion: This report demonstrates the utility of virtual neuromuscular ultrasound courses for those participants willing to respond to a survey and describes a proposed design for such courses. Although hands‐on supervised ultrasound training is ideal, virtual courses can be useful alternatives to in‐person training when in‐person interaction is restricted. Abstract : See Editorial on pages 1‐3 in this issue .